2017
DOI: 10.1002/jcb.26426
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: MicroRNA‐29a inhibits proliferation and motility of schwannoma cells by targeting CDK6

Abstract: MicroRNA-29 (miR-29) family is involved in various types of cancer regulation. Although miR-29 family was shown to play an inhibitory role in tumorigenesis, the effect of miR-29a expression on schwannoma cells still remains unclear. In this study, we aimed to explore the role of miR-29 family in schwannoma. The expressions of miR-29a, miR-29b, and miR-29c were detected in the Schwann tissues and cell lines using qRT-PCR. The effect of miR-29a, miR-29b, and miR-29c on cell viability, migration, invasion, and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In schwannoma, miR-29a has been shown to downregulate CDK6 expression and disrupt cell cycle progression by the deactivation of JNK and p38MAPK/ERK pathways. Overexpression of all three members of the miR-29 family in Schwann cells inhibited cell viability, migration, and invasion in vitro 113 …”
Section: Main Textmentioning
confidence: 98%
“…In schwannoma, miR-29a has been shown to downregulate CDK6 expression and disrupt cell cycle progression by the deactivation of JNK and p38MAPK/ERK pathways. Overexpression of all three members of the miR-29 family in Schwann cells inhibited cell viability, migration, and invasion in vitro 113 …”
Section: Main Textmentioning
confidence: 98%
“…MiR-29 family ( miR-29a, miR-29b , and miR-29c ) was connected with aggressiveness and prognosis of malignant neoplasms and might act as a considerable biomarker for forecasting the recurrence and progression of cancers [ 12 15 ]. Nonetheless, from articles we have learnt that miR-29a and miR-29b appeared to be more effective than miR-29c in targetting genes and signaling pathways [ 16 , 17 ]. The role of miR-29b in cancers had been fully discussed by Yan et al [ 18 ] in 2015 and the new progression of miR-29b was less.…”
Section: Introductionmentioning
confidence: 99%
“…Shin et al found that miR-29b effect on glioblastoma was suppressive (21). Ma et al stated that, miR-29 suppressed schwannoma cell proliferation and motility by regulating CDK6 (22). In colon cancer, miR-29 showed inhibitory effect on cell invasion and migration by regulating MMP2 (23).…”
Section: Introductionmentioning
confidence: 99%